Championing gender in agricultural services in Kenya - Bikketi, Edward; Gumucio, Tatiana; Cecchi, Francesco; Kramer, Berber; Waithaka, Lilian; Waweru, Carol (International Food Policy Research Institute, 2022)
Key messages: • Champion farmers are male and female influencers recruited to support the delivery of agricultural services to fellow farmers within their communities (including seeds, advisories, and crop insurance), thereby promoting gender and social inclusion. • Providing insurance as a stand-alone product is too expensive to build a sustainable and cost-effective champion farmer model; there is a need to integrate the model with other services, including the provision of seeds, and to leverage government subsidies. • Champion farmers face steep competition from other service providers in the provision of seeds, but their networks give them opportunities to tap into underserved markets, as they have connections with women-led farmer collectives. • Female champion farmers’ socially ascribed gender roles and responsibilities related to homecare contribute to time poverty and drudgery and potentially inhibit the extent to which women can benefit from their champion role. • It is necessary to promote a better understanding of insurance among farmers and build farmers’ trust in services and products through additional training of champion farmers, sensitization of farmers, and awareness creation.